A study on outcome of pregnancy of unknown location - Rahim, Maryam; Aggarwal, Shikha; Rathi, Neelam; Debnath, Parikshit; Maji, Debkalyan (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Pregnancies of unknown location (PUL) are becoming more common as women presenting to early pregnancy assessment units when a pregnancy test comes positive but there is no evidence of an intrauterine pregnancy. The objective of the present retrospective study was to find out the outcome of women with pregnancy of unknown location presenting to a tertiary hospital in Northern Ireland. Methods: This retrospective analytic study used medical record data between July 2019 and December 2021 from the Altnagelvin Area Hospital of Northern Ireland. TVUS was considered to diagnose the PUL and thereafter beta-human chorionic gonadotrophin (β-hCG) level was monitored as per institutional protocol. Expectant management was carried out until the pregnancy outcome was finalised. Using Statistical package for social sciences (SPSS) version 26, all collected data were analysed using the multinomial logistic regression. Results: For the analysis among the 63 participants, 25.4% were primi gravida and 38.1% presented with 4-5 weeks of gestation. Pain abdomen and vaginal bleeding was represented by 20.6% and 52.4% respectively. Confirmed ectopic pregnancy was observed among 4.8% and was surgically managed. Also, persistent PUL was 7.9% and these cases were successfully managed by Methotrexate. Conclusions: The large proportion will be biochemical pregnancy or intrauterine pregnancies, with a tiny fraction of ectopic pregnancies. Early detection of ectopic pregnancy is most challenging part among the women presented with PUL category.